Breast Reconstruction 2016
DOI: 10.1007/978-3-319-18726-6_112
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Sparing TRAM Flap Does Not Protect Breast Reconstruction from Postmastectomy Radiation Damage Compared with the DIEP Flap

Abstract: BACKGROUND-Radiation to free flaps following immediate breast reconstruction has been shown to compromise outcomes. We hypothesized that irradiated muscle-sparing free transverse rectus abdominis musculocutaneous (MS FTRAM) flaps experience less fat necrosis than irradiated deep inferior epigastric perforator (DIEP) flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 52 publications
(65 reference statements)
0
19
1
5
Order By: Relevance
“…Thirty-five articles included complications and/or reconstruction failures in device-based reconstructions [4][5][6]10,11,. Twenty-seven articles included complications or reconstructive failures in autologous reconstructions [4,5,9,12,[15][16][17][18][19]28,39,40,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. A detailed analysis of complications is depicted by method of reconstruction in Table III. A comparison of complications between device-based and autologous reconstructions in the setting of PMRT demonstrated that device-based reconstruction had a significantly higher incidence of infection (13.5% vs. 5.8%; P < 0.0001), mastectomy flap necrosis (10.5% vs. 5.0%; P ¼ 0.03), re-operation due to complication (37.0% vs. 16.6%; P ¼ <0.0001), and total complications (41.3% vs. 30.9%; P < 0.0001).…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…Thirty-five articles included complications and/or reconstruction failures in device-based reconstructions [4][5][6]10,11,. Twenty-seven articles included complications or reconstructive failures in autologous reconstructions [4,5,9,12,[15][16][17][18][19]28,39,40,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. A detailed analysis of complications is depicted by method of reconstruction in Table III. A comparison of complications between device-based and autologous reconstructions in the setting of PMRT demonstrated that device-based reconstruction had a significantly higher incidence of infection (13.5% vs. 5.8%; P < 0.0001), mastectomy flap necrosis (10.5% vs. 5.0%; P ¼ 0.03), re-operation due to complication (37.0% vs. 16.6%; P ¼ <0.0001), and total complications (41.3% vs. 30.9%; P < 0.0001).…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…Fourteen recent studies evaluating radiation-associated complications of autologous reconstruction are included in this review, with 12 providing level III evidence and the remaining 2 providing level IV evidence (Table II). Of these, 9 reported complications following immediate reconstruction and post-operative PMRT [11,25,45,[47][48][49][50][51][52]. In these studies, a wide variation was observed in reported rates of volume loss or shrinkage that ranged from 6% to 87.5%, and incidences of contracture or contour deformities ranged from 12.6% to 75%.…”
Section: Surgical Outcomesmentioning
confidence: 99%
“…19,40,41 Existing data on autologous reconstruction and PMRT found an increased odds of fat necrosis and volume loss, but acceptable results with regard to complications. 21,[41][42][43][44][45] In patients who elect to undergo immediate breast reconstruction, the potential need for PMRT should be determined before surgery to diminish the risks of unexpected indication for PMRT and preserve patient satisfaction. Clinical decision-making regarding the need for PMRT and immediate breast reconstruction requires a multidisciplinary approach and careful patient counseling.…”
Section: Discussionmentioning
confidence: 99%